Teacher's Strategy in Improving Students' Digital Literacy in Islamic Religious Lessons at State Islamic Senior High School (MAN) Rejang Lebong - Deri Wanto; Ririn Eka Monicha (ISTAWA, 2025)
Digital literacy is the ability and expertise to access and use information from various digital sources or references. The purpose of this study is to find out the strategies or methods of teachers in improving students' digital literacy in Islamic religious lessons. This research uses descriptive qualitative method. The conclusion is that the teacher's strategy in improving students' digital literacy at State Islamic Senior High School Â Rejang Lebong has gone well by providing assignments that are in accordance with the material studied by students, where students can access, select, understand, and analyze various learning resources based on the Al-Qur'an. Â And Hadith. The advice given is that teachers continue to provide knowledge or guidance regarding digital literacy for the material presented so that it remains effective, smart and wise in using digital media.